Conversion of glucose into lactic acid using silica-supported zinc oxide as solid acid catalyst - Lau, Kam Sheng; Chia, Chin Hua; Chin, Siew Xian; Chook, Soon Wei; Zakaria, Sarani; Juan, Joon Ching (De Gruyter, 2018)
Zinc oxide (ZnO) has been proven to be highly effective in converting biomass into fine chemicals. It possesses several limitations, such as leaching in hydrothermal reactions and difficulty with regard to its recovery. Supporting ZnO on silica improves its recovery, stability and recyclability. In this study, we produced silica-supported ZnO by incipient wetness impregnation (IWI) method for the conversion of glucose into lactic acid. The presence of the ZnO provided active sites for isomerization to occur. The highest yield of lactic acid was 39.2 % at 180 °C for 60 min. Prolonged reaction time and higher reaction temperature promoted further degradation of lactic acid into acetic acid. The yield of lactic acid decreased after the first cycle and decreased slightly for the nine consecutive cycles.